2008
DOI: 10.1021/jp711051e
|View full text |Cite
|
Sign up to set email alerts
|

Chain Growth Mechanism in Fischer−Tropsch Synthesis:  A DFT Study of C−C Coupling over Ru, Fe, Rh, and Re Surfaces

Abstract: A quantitative approach is used to understand the chain growth mechanism in FT synthesis on the Ru, Fe, Rh, and Re surfaces. The C−C coupling reactions are extensively calculated on the stepped metal surfaces. Combining the coupling barriers and reactant stabilities, we investigate the reaction rates of all possible C1 + C1 coupling pathways on the metal surfaces. It is found that (i) all the transition-state structures are similar on these surfaces, while some coupling barriers are very different; (ii) the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 45 publications
12
125
0
1
Order By: Relevance
“…The first layer is , the second layer , the third layer and the forth layer of chain propagation and termination is crucial for the production of desired products. Although it is difficult to simulate the elementary steps involving large molecules on the catalyst surface due to the limitation of current computational capacity, some theoretical efforts [36,37,116,119,120,143] have been devoted to this field concerning the formation of C 2 and C 3 . Hu and coworker have investigated all the possible reaction pathways for C 1 ?…”
Section: Chain Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The first layer is , the second layer , the third layer and the forth layer of chain propagation and termination is crucial for the production of desired products. Although it is difficult to simulate the elementary steps involving large molecules on the catalyst surface due to the limitation of current computational capacity, some theoretical efforts [36,37,116,119,120,143] have been devoted to this field concerning the formation of C 2 and C 3 . Hu and coworker have investigated all the possible reaction pathways for C 1 ?…”
Section: Chain Growthmentioning
confidence: 99%
“…More importantly, it can distinguish between those possibilities that were left open, such as various reaction pathways. Since the mechanism of FTS is inconclusive and controversial, more and more DFT calculations have been devoted to tackle these issues [18,19], especially for the mechanism of CO activation [27][28][29][30][31], methane formation [32][33][34][35], and chain growth [36][37][38]. Despite the successful implementations of DFT in catalysis process, it still holds some drawbacks such as failure in the calculation of weak interactions (such as Van der Waals interaction) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some of our recent work have focused on the fundamental issues mentioned above in FT synthesis, aiming to provide some insight into improving catalysts towards higher activity and better selectivity [24][25][26][27][28][29][30][31]. This paper is mainly a short review of our previous work on FT synthesis, aiming to provide a coherent picture of FT synthesis from DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations were also used in studies of the mechanisms of hydrocarbon chain growth and chain termination, which are essential aspects in the synthesis of long chain hydrocarbons and oxygenated compounds through the Fischer-Tropsch process [57,58,74]. The reaction routes proposed are the carbide (also known as alkyl mechanism) and the CO insertion mechanisms, cf.…”
Section: Co* + H* → Coh* + * (3a)mentioning
confidence: 99%
“…An overview of such routes can be found in the work of Davis et al [7]. Cheng et al [57,58] investigated by DFT which are the CHx intermediates that are preferentially coupled during the hydrocarbon chain growth on stepped Co, Rh, Ru, Fe and Re surfaces via the carbide mechanism. They found that despite the transition state structures are quite similar, the energy barriers for the different C-C coupling reactions differ considerably among the transition metals considered in their work, which leads to different preferential paths for the chain growth in each metal.…”
Section: Co* + H* → Coh* + * (3a)mentioning
confidence: 99%